INDUSTRI KREATIF FASHION - Utami, Restu; Restuadhi, Hendri (JUSS (Jurnal Sosial Soedirman), 2017)
The article deals with the phenomenon of creative industries in Purwokerto, particularly fashion. It focuses on the survival strategy and idealism of Kidal Kolektif, one of fashion outlets in Purwokerto. This article selects to analyze Kidal Kolektif as the outlet has uniqueness incomparable to other fashion outlets in Purwokerto. Kidal Kolektif is a social economic movement attempting to create independence through fashion business. It also has a specific feature as they attempt to nurture idealism in their distinctive product designs. In their efforts to develop their business, a part of their survival is undertaking partnerships with other organizations in form of profit sharing. The other part is being persistent with their esteem that every human being would be able to fulfill their need by working with their own interest, talent, and need, and maintain their economic independence.